Neotropical species of Elpidium F. Müller, 1880 (Crustacea: Ostracoda) introduced into New Caledonia (Melanesia, Pacific Ocean) through ornamental bromeliad trade - Pereira, Julia Da Silva; Pinto, Ricardo Lourenço; Cruz-Rivera, Edwin; Cunha, Maria Eduarda Bernardino; Martens, Koen; Higuti, Janet (Zootaxa, 2026)
The ostracod genus Elpidium is known so far for South and Insular America and all of its 20 known species are confined to phytotelmata, mostly in tank-bromeliads. These plants, with more than 1200 species in the Atlantic Forest along the eastern shores of Brazil, can be either terrestrial or epiphytic, and occur along a vast altitudinal gradient. In recent decades, an international, even intercontinental, trade in ornamental bromeliads has expanded. These plants can be transported over large distances, and in some cases contain “passenger” taxa in their tanks, mostly insects and crustaceans. Here, we report on the discovery of two species of Elpidium from bromeliad phytotelmata in New Caledonia (Melanesia, Pacific Ocean). By coincidence, the same two species had also recently been collected from their presumed native area, one from Insular America (Dominican Republic and US Virgin Islands) and one from South America (Itapeva park in southern Brazil). These two species, Elpidium alarconi Mesquita-Joanes et al., 2025 and Elpidium itapevaense sp. nov., are here reported and (re-) described. Morphological comparisons with the populations from New Caledonia are provided.